The Effect of Role Playing Method on Conflict Resolution Learning in Elementary School - Sinta Maria Dewi (Jurnal Sekolah Dasar, 2021)
This study aims to determine the effect of the role playing method on learning conflict resolution in elementary schools. The research method used is a quasi-experimental method. Data collection through pretest and posttest. Based on the results of research and data analysis, the pretest average experimental class was 49.4 and the control class was 48.25. After being given treatment and doing a posttest that the experimental results were 68.1 higher than the control class average value of 54.75. The calculation of the hypothesis using t-test, namely the paired sample T test and obtained at a significant level of 0.05 indicates that the probability value (significance) is 0.00. because of the significance value, Ho is rejected. This proves that the use of the role playing learning model affects the conflict resolution skills of fourth grade students of SDN Anggadita V. From the results of this study the researcher hopes to contribute and benefit to all parties involved, especially the school in order to provide conflict resolution learning to elementary school children so that students have skills in solving problems so that it can be beneficial for their daily life and their future.